Traffic accessibility and the effect on firms and population in 99 Austrian regions - Wolfgang Polasek; Wolfgang Schwarzbauer (Institute for Advanced Studies (IHS), 2006)
In this paper we describe the EAR (regional economic accessibility) model to investigate the impact of the improvement of railroad infrastructure on regional GDP, population and firms growth in 99 Austrian regions. We evaluate the impact of four potential railroad infrastructure investment projects on the accessibility of Austrian regions, which is used to forecast future growth of these regions. Regional performance is measured by four variables, gross regional product, number of firms, population size, and employment. Eventually a ranking of these four projects is carried out for the first ten years of operation of the four potential investment projects. We show that the improvement of train accessibility has different impacts on regions with high and low overall performance.
Keywords: R1; R41; L92; C21; C23; 330; evaluation of infrastructure projects; long-term regional forecasts; accessibility and traffic analysis; ranking; Verkehrsinvestition; Streckenbau; Makroökonomischer Einfluss; Regionales Wachstum; Verkehrsinfrastrukturpolitik; Österreich